Environmental engineering - Weiner, Ruth F.; Matthews, Robin A.; Vesilind, P. Aarne (Amsterdam ; Boston : Butterworth-Heinemann, 2003)
This book provides a comprehensive introduction to air, water, noise, and radioactive materials pollution and its control. Legal and regulatory principles and risk analysis are included in addition to engineering principles. The text presents the engineering principles governing the generation and control of air and water pollutants, solid and hazardous waste, and noise. Water quality and drinking water treatment are discussed, as well as the elements of risk analysis. Radioactive waste generation and treatment in relation to the nuclear fuel cycle, are discussed. The health and environmental effects of all these pollutants are discussed. An introduction to the Federal laws and regulations governing pollution is included. - This text embraces the latest thinking in environmental engineering - Includes updates in regulation and current pollution abatement technologies.
Environmental engineering -- Assessing environmental impact -- Risk analysis -- Water pollution -- Measurement of water quality -- Water supply -- Water treatment -- Collection of wastewater -- Wastewater treatment -- Sludge treatment and disposal -- Nonpoint source water pollution -- Solid waste -- Solid waste disposal -- Reuse, recycling, and resource recovery -- Hazardous waste -- Radioactive waste -- Solid and hazardous waste law -- Meteorology and air pollution -- Measurement of air quality -- Air pollution control -- Air pollution law -- Noise pollution.
Rev. ed. of: Environmental engineering / P. Aarne Vesilind. 3rd ed. c1994.
Includes bibliographical references (p. 465-470) and index.
Keywords: Environmental engineering; Electronic books